Harmonized commodity description and coding system : alphabetical index (World Customs Organization BrusselsBE, 2017)
Consists of an alphabetical listing of the articles and products mentioned in the Harmonized Commodity Description and Coding System (Harmonised System) and its explanatory notes.
v.1 : A to L. - v.2 : M to Z